Survey and identification of insect pests of oyster mushroom (Pleurotus ostreatus) cultures in central province of Sri Lanka - Gnaneswaran, R.; Wijayagunasekara, H.N.P. (Tropical Agricultural Research and Extension., 1999)
Mushroom cultivation in Sri Lanka was established as a profitable small industry only after 1986. The continuous growing of mushrooms on a large scale in localized areas had led to various pest infestations. The present study was conducted to investigate the pest spectrum of oyster mushroom [Pleurotus ostreatus (Jacq. fr.)] with the aim of recognizing the key pests in commercial mushroom cultivation in Sri Lanka. Twenty-two mushroom houses from Central Province of Sri Lanka were selected for the study. Nine species of insects were found to be associated with mushroom cultures. Among them only three species namely Drosophila funebris F., Bradysia papuera Tuomikoski and CyUodes bifacies (Walker) were found to cause some damage. CyUodes bifacies was distributed in about 96 per cent of the farms visited causing serious damage up to 82 per cent. It was identified as the key pest of mushrooms grown in the Central Province. This is the first instance that C. bifacies has been found on cultivated mushrooms. Although Drosophila funebris is considered as an occasional insect pest on mushroom it was identified as a major pest. Bradysia paupera was found to be a minor pest in this area.
Keywords: Bradysia paupera; CyUodes bifacies; Drosophilafunebris; Insect pest; Mycodrosophila sp.; Pleurotus; Ostreatus